Interventions in ambulatory healthcare settings to reduce social isolation among adults aged 18–64: a systematic review - Kavya Anchuri; Liane Steiner; Roxana Rabet; Amy Craig-Neil; Ellah San Antonio; Oluwasegun Jko Ogundele; Melanie Seabrook; Ceinwen Pope; Serina Dai; Andree Schuler; Carolyn Ziegler; Andrew David Pinto (BJGP Open)
Background: Social isolation is associated with increased all-cause and premature mortality, poor chronic disease management, and mental health concerns. Limited research exists on interventions addressing social isolation among individuals under 65 despite its increasing prevalence among young and middle-aged adults. Aim: To identify interventions from the extant literature that address social isolation and loneliness in ambulatory healthcare settings in adults aged 18–64 and to identify elements of successful studies for future intervention design. Design & setting: Systematic review of interventions targeting social isolation in community-dwelling adults aged 18–64 within ambulatory healthcare settings. Method: A search strategy was developed to identify relevant articles in the following databases: Ovid MEDLINE, Embase, EBM Reviews, Scopus, CINAHL, and PsychInfo. Data were extracted on study design and setting, intervention type, outcome related to social isolation/loneliness, and scale of measure used. Results: 25 078 citations were identified and underwent title and abstract screening. 75 articles met our inclusion criteria and were synthesised, including an assessment of bias. Effective interventions were delivered in community health settings, incorporated a group component, and used digital technologies. They also addressed the association between mental health and social isolation using cognitive-behavioural therapy (CBT) approaches and enhanced self-management and coping strategies for chronic conditions through psycho-educational interventions. Conclusion: Future research should prioritise adults living in low-income and middle-income countries, racialised individuals, as well as those with fewer educational opportunities. There is also a need to advance research in primary care settings, where longitudinal patient–provider relationships would facilitate the success of interventions.